PREPARATION OF LEAD ZIRCONATE TITANATE FILM BY SOL-GEL METHOD AND ITS CHARACTERIZATION - Silvester Tursiloadi; Hiroaki Imai; Hiroshi Hirashima (Research Center for Chemistry - LIPI, 1996)
A ferroelectric material film of Lead Zirconate Titanate, Pb(Zr,Ti)O3 (PZT), was produced by sol-gel method from alkoxide and acetate precursors in a normal propanol solvent system. The excess amount of Pb was 10 mole % more than stoichiometrically used for preparing the solution. The concentration of PZT in coating solution was 0.7 M, and pH of the solution was 4.5. The films was prepared by dip-coating onto slide glass, silica glass and Pt/Ti/SiO2/Si substrate. In order to avoid cracking TiO2 was coated on the glasses as a barrier layer. The asdried PZT film was amorphous from X-ray diffraction. The amount of pyrochlore and perovskite phase depended on the heating temperature and kind of barrier layer. Single perovskite phase was found for coated films on TiO2/SiO2 and Pt/Ti/SiO2/Si heated at 600° C or higher, but it was never found for coated films on SiO2 substrate without barrier layers. Crystallization of perovskite PZT film was retarded when deposited on amorphous substrates as compared to crystalline substrate. The coated film on Pt/Til/SiO2/Si was thicker and smaller in particle size than that of coated film on Ti02/SiO2. A columnar structure with a diameter around 6.5 nm, was observed and no boundary was observed between layers in 9 time dipcoated film on Pt/Ti/SiO2/Si.